Metabolic changes in adipose tissues in response to β3‐adrenergic receptor activation in mice. Issue 1 (6th September 2018) - Fujimoto, Yusuke; Hashimoto, Osamu; Shindo, Daichi; Sugiyama, Makoto; Tomonaga, Shozo; Murakami, Masaru; Matsui, Tohru; Funaba, Masayuki
Abstract: Brown and beige adipocytes dissipate energy as heat. Thus, the activation of brown adipocytes and the emergence of beige adipocytes in white adipose tissue (WAT) are suggested to be useful for preventing and treating obesity. Although β3 ‐adrenergic receptor activation is known to stimulate lipolysis and activation of brown and beige adipocytes, fat depot–dependent changes in metabolite concentrations are not fully elucidated. The current study examined the effect of treatment with CL‐316, 243, a β3 ‐adrenergic receptor agonist, on the relative abundance of metabolites in interscapular brown adipose tissue (iBAT), inguinal WAT (ingWAT), and epididymal WAT (epiWAT). Intraperitoneal injection of CL‐316, 243 (1 mg/kg) for 3 consecutive days increased the relative abundance of several glycolysis‐related metabolites in all examined fat depots. The cellular concentrations of metabolites involved in the citric acid cycle and of free amino acids were also increased in epiWAT by CL‐316, 243. CL‐316, 243 increased the expression levels of several enzymes and transporters related to glucose metabolism and amino acid catabolism in ingWAT and iBAT but not in epiWAT. CL‐316, 243 also induced the emergence of more beige adipocytes in ingWAT than in epiWAT. Furthermore, adipocytes surrounded by macrophages were detected in the epiWAT of mice given CL‐316, 243. The current study reveals the fat depot–dependent modulation of cellular metabolites in CL‐316, 243‐treated mice, presumably resulting from differential regulation of cell metabolism in different cell populations. Abstract : The current study examined the effect of treatment with CL‐316, 243, a β3‐adrenergic receptor agonist (Adrb3), on the relative abundance of metabolites in interscapular brown adipose tissue (iBAT), inguinal WAT (ingWAT), and epididymal WAT (epiWAT). As a result, we show the fat depot–dependent modulation of cellular metabolites in CL‐316, 243‐treated mice, presumably resulting from differential regulation of cell metabolism in different cell populations.